PENGARUH VARIETAS DAN BAHAN ORGANIK TERHADAP JUMLAH ANAKAN DAN PRODUKSI PADI SAWAH IP 400 FASE VEGETATIF MUSIM TANAM I - Timbul Simbolon; Posma Marbun; Fauzi Fauzi (Jurnal Agroekoteknologi, 2013)
This research was aimed to determine whether composting organic materials and varieties of riceplants of different IP 400 can reduce the rate of air temperature in rice vegetative phase and also toknow which varieties or organic matter are likely to be better in reducing the rate of air temperatureand increase rice production IP 400. This research was conducted in paddy fields and DevelopmentResearch Institute, Village Market District Leaning Fence Merbau Deli Serdang (30 29 '51.33 "Nand 980 54' 19.87" E) with a height of 30 meters above sea level where conducted from February2012 to complete. This research used a randomized block design factorial with six combinations oftreatments and three replications thus obtained eighteen experimental unit. Treatment consists ofV1B0 (Inpari 1 + Without Organic Materials), V1B1 (Inpari 1 + straw compost 9 kg), V1B2 (Inpari 1+ Cow Manure 9 kg), V2B0 (Ciherang + Without Organic Materials), V2B1 (Ciherang + Compoststraw 9 kg), V2B2 (Ciherang + Cow manure 9 kg). The results of this research indicate varieties ofrice IP 400 and composted organic materials that have been able to suppress the air temperature andincrease rice production IP 400, but did not suppress emission rate at 35 days after planting.Keywords: IP 400, cow manure, straw compost, air temperature